2020
DOI: 10.1177/2165079920925505
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Objective and Self-Reported Levels of Physical Activity Among Florida Firefighters Across Weight Status Category: A Cross-Sectional Pilot Study

Abstract: Background: Firefighters suffer from a disproportionally high burden of chronic diseases that could be prevented from regular bouts of physical activity (PA). The goal(s) of this pilot study were to (a) describe typical PA levels in professional paid firefighters, and (b) assess their ability to estimate their own levels of PA. Methods: A repeated measures study design was used to assess self-reported and objectively measured levels of PA from a non-probabilistic sample of firefighters ( n = 18) over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Second, the construct validity of the SIMPAQ and PAVS are still unknown in firefighters. Previous research demonstrated that, compared with objective assessments, firefighters tend to overestimate their physical activity levels (Kling et al, 2020). Consequently, future research should include objective physical activity assessment tools such as accelerometers or other, for example, wrist-wearable activity tracking devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the construct validity of the SIMPAQ and PAVS are still unknown in firefighters. Previous research demonstrated that, compared with objective assessments, firefighters tend to overestimate their physical activity levels (Kling et al, 2020). Consequently, future research should include objective physical activity assessment tools such as accelerometers or other, for example, wrist-wearable activity tracking devices.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to adversity and potentially traumatic events on a regular basis can result in chronic mental and physical conditions (Obuobi-Donkor et al, 2022). Furthermore, an inactive lifestyle has also been reported as an important mental and physical health risk factor in firefighters (Choi et al, 2016; Kling et al, 2020; Ras & Leach, 2022). Firefighters spend most of their working time physically inactive at the fire station as well as during their off-duty leisure time (Barry et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These include fire suppression activities, rescue operations, and delivering emergency medical services. 6,7 Current scientific literature suggests that US firefighters already suffer from a disproportionate burden of health conditions and negative health behaviors including cardiovascular disease, [8][9][10] respiratory disease, [11][12][13] cancer, [14][15][16] musculoskeletal disorders, [17][18][19] sedentary behaviors while on-shift, [20][21][22] and binge drinking. [1][2][3] Drinking behaviors among firefighters is concerning, given excess alcohol consumption has been linked to some of these chronic health diseases that have been documented in the firefighter workforce.…”
mentioning
confidence: 99%
“…In addition to binge drinking, obesity is a major concern in the US firefighter workforce 22–29 . Approximately 78% of firefighters can be categorized into the combined overweight and obese weight class 23 .…”
mentioning
confidence: 99%
See 1 more Smart Citation